Parent-infant affect synchrony during social and solo play - Kidby, Sayaka (2023)
While mother-infant affect synchrony has been proposed to facilitate the early development of social understanding, most investigations into affect synchrony have concentrated more on negative than positive affect. We analysed affect sharing during parent-infant object play, comparing positive and negative affect, to examine how it is modulated by shared playful activity. Mother-infant dyads (N = 20, average infant age 10.7 months) played together (social) or separately (solo) using an object. Both participants increased positive affect during social play as compared with solo play. Positive affect synchrony also increased during social play compared with solo play, whereas negative affect synchrony did not differ. Closer examination of the temporal dynamics of affect changes showed that infants' shifts to positive affect tended to occur contingently in response to their mothers', whereas mothers' shifts to negative affect followed their infants'. Further, during social play, positive affect displays were more long-lived while negative more short-lived. While our sample was small and from a homogeneous population (e.g. white, highly educated parents), limiting the implications of the findings, these results demonstrate that maternal active engagement in playful interaction with her infant affords, increases, and extends infant positive affect and parent-infant positive affect synchrony, providing insights into how the social context modulates infants' affective experiences. This article is part of a discussion meeting issue 'Face2face: advancing the science of social interaction'.